Wolbachia-induced meiotic drive and feminization is associated with an independent occurrence of selective mitochondrial sweep in a butterfly. (31st May 2017) - Miyata, Mai; Konagaya, Tatsuro; Yukuhiro, Kenji; Nomura, Masashi; Kageyama, Daisuke
Abstract : Maternally inherited Wolbachia endosymbionts manipulate arthropod reproduction in various ways. In the butterfly Eurema mandarina, a cytoplasmic incompatibility-inducing Wolbachia strain w CI and the associated mtDNA haplotypes are known to originate from the sister species Eurema hecabe, which offered a good case study for microbe-mediated hybrid introgression. Besides w CI, some females with the Z0 karyotype harbour a distinct Wolbachia strain w Fem, which causes all-female production by meiotic drive and feminization. We report that a considerable proportion of E. mandarina females (65.7%) were infected with both w CI and w Fem (CF) on Tanegashima Island. While females singly infected with w CI (C) produced offspring at a 1 : 1 sex ratio, CF females produced only females. Although Z-linked sequence polymorphism showed no signs of divergence between C and CF females, mtDNA split into two discrete clades; one consisted of C females and the other CF females, both of which formed a clade with E. hecabe but not with uninfected E. mandarina . This suggests that CF matrilines also, but independently, experienced a selective sweep after hybrid introgression from E. hecabe . Distinct evolutionary forces were suggested to have caused C and CF matrilines to diverge, which would be irreversible because of the particular phenotype of w Fem.